Imidazolium Based Ionic Liquids: Impact of the Cation Symmetry and Alkyl Chain Length on the Enthalpy of Vaporization. Issue 1 (8th November 2016) - Yermalayeu, Andrei V.; Zaitsau, Dzmitry H.; Loor, Manuel; Schaumann, Julian; Emel'yanenko, Vladimir N.; Schulz, Stephan; Verevkin, Sergey P.
Abstract : The vaporization thermodynamics of symmetric imidazolium based ionic liquids of the general formula [C n C n Im][Br] with the chains length n = 4, 5, 6, and 8 were investigated using a combination of DSC, TGA, and QCM methods with quantum chemical calculations. Comparison of vaporization enthalpies for the symmetric ([C n C n Im][Br]) and asymmetric imidazolium based ILs ([C n mim][Br]) revealed a general trend with the lower vaporization enthalpies of the symmetric species indicating a significant decrease of the Coulombic interactions affecting energetics of vaporization. Abstract :